Hypercalcemia of advanced chronic liver disease: a forgotten clinical entity! - Kuchay, Mohammad Shafi (Clin Cases Miner Bone Metab, 2016)
Hypercalcemia caused by advanced chronic liver disease (CLD) without hepatic neoplasia is uncommonly reported and poorly understood condition. We are reporting two cases of advanced CLD who developed hypercalcemia in the course of the disease. This diagnosis of exclusion was made only after meticulous ruling out of all causes of hypercalcemia. The unique feature of this type of hypercalcemia is its transient nature that may or may not require treatment. This clinical condition in patients with CLD should be kept in mind while evaluating the cause of hypercalcemia in them.